The Effects of Brain Gym and Coloring Pictures on Cognitive Functions of the Elderly - Lilik Pranata; Aniska Indah Fari; Sri Indaryati (Media Karya Kesehatan, 2021)
Elderly phase is the final process of human age in growth and development. Aging is a change that impacts physical and cognitive functions. The decrease of cognitive functions can interfere with all activities of the elderly. The objective of this research is to investigate the effects of brain gym and coloring pictures on the cognitive functions of the elderly. This study used a quasi-experimental design with a pre-test and post-test without a control group. Purposive sampling was applied to select the respondents at an elderly nursing home. The total sample was 30 respondents that included 15 respondents of the brain gym intervention group and 15 respondents of the coloring picture intervention group. The results showed that there was no significant difference in cognitive function before and after the intervention given to the coloring picture group with the p-value 0.414> α (0.05). Meanwhile, there was a significant difference in cognitive function before and after the intervention given to the brain gym group with the p-value 0.025 <α (0.05). The management of nursing home should provide the brain gym activities to improve the cognitive functions of the elderly.Keywords: The elderly, brain gym, coloring pictures.